2016
DOI: 10.1021/acs.jpcc.6b05012
|View full text |Cite
|
Sign up to set email alerts
|

Structure Formation and Thermal Stability of Mono- and Multilayers of Ethylene Carbonate on Cu(111): A Model Study of the Electrode|Electrolyte Interface

Abstract: In this work, we aim at a molecular scale understanding of the interactions and structure formation at the electrode|electrolyte interface (EEI) in Li-ion batteries. Therefore, the interaction of the key electrolyte component ethylene carbonate (EC) with Cu(111) was investigated under ultrahigh vacuum conditions. Scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIRS), and dispersion-corrected density functional theory (DFT-D) calculations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 63 publications
10
20
0
1
Order By: Relevance
“…[49] Finally,t he small peak at 288.5 eV can be ascribed to C=Of ragments,w hich are most probably related to EC/DMC or their decomposition products. [50] Thes pectra in the C1sr egion arev ery similar with regard to intensity,p eak shape,a nd position for all three SOCs studied. Based on these findings,w ee xcludet he build-up of an extendedS EI film during cycling, which is usuallyf ormed at the electrode surface at high potentials and contains chemical species such as ROCO 2 Li, ROLi, or polycarbonates.…”
Section: Resultsmentioning
confidence: 71%
“…[49] Finally,t he small peak at 288.5 eV can be ascribed to C=Of ragments,w hich are most probably related to EC/DMC or their decomposition products. [50] Thes pectra in the C1sr egion arev ery similar with regard to intensity,p eak shape,a nd position for all three SOCs studied. Based on these findings,w ee xcludet he build-up of an extendedS EI film during cycling, which is usuallyf ormed at the electrode surface at high potentials and contains chemical species such as ROCO 2 Li, ROLi, or polycarbonates.…”
Section: Resultsmentioning
confidence: 71%
“…Very likely, the peak at the highest binding energy (289.1 eV) is related to residual solvent from the rinsing process. 39 The peak at 286.5 eV can be associated with the oxidation of graphite C atoms, occurring upon the intercalation of AlCl 4 À . This is in agreement with the well-known redox-amphoteric behavior of graphite when used as intercalation host.…”
Section: Resultsmentioning
confidence: 99%
“…One possible way to determine the initial stages of the SEI formation at the EEI at the atomic/molecular level involves the use of surface science techniques, studying the interaction of individual components of electrolytes, such as the typical key component EC (or other electrolyte components like ionic liquids), with well‐defined model electrodes under idealized ultrahigh‐vacuum (UHV) conditions, which is focus of the ongoing work in our laboratory. Following a previous study on the interaction of EC with Li‐free and lithiated highly oriented pyrolytic graphite (HOPG) as model for the anode, we here report the results of a similar type of study on the interaction of EC with well‐defined LiCoO 2 electrode surfaces, both fully oxidized LiCoO 2 and partly reduced LiCoO 2− δ surfaces, as models for the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…This was derived from desorption of fragments like C 2 H 4 , C 2 H 4 O, and CO 2 , upon heating (possible products of the above Li‐containing species). Using scanning tunneling microscopy and X‐ray photoelectron spectroscopy (XPS) in combination with dispersion‐corrected density functional theory calculations to study the interaction of ultrathin EC films with Cu(111), we found that adsorbed EC molecules self‐assemble into a well‐ordered 2D arrangement on Cu(111) at 80 K, and that competing desorption and decomposition set in at ≈170 K . Studies on the interaction of battery‐relevant solvents with LiCoO 2 have been conducted for DEC, water, and dimethyl sulfoxide (DMSO) with the samples cooled to ≈110 K .…”
Section: Introductionmentioning
confidence: 99%